COMPARATIVE EFFECTIVENESS OF OPIOID-FREE ANESTHESIA AND OPIOID-BASED ANESTHESIA ON THE INCIDENCE OF POSTOPERATIVE NAUSEA AND VOMITING: A SYSTEMATIC REVIEW - Adi Widarma, I Made Agus; Sudiantara, Putu Herdita; Ulandari, Komang Sherly; Habisena, Cokorda Gde Waesa; Pratama, Pande Putu Arista Indra (UNG, 2026)
Perioperative pain management commonly relies on opioids, which are associated with significant adverse effects, particularly postoperative nausea and vomiting (PONV), affecting up to 80% of high-risk surgical patients. This systematic review aimed to compare the effectiveness of opioid-free anesthesia (OFA) and opioid-based anesthesia (OBA) in reducing PONV incidence. This systematic review followed the PRISMA guidelines. A comprehensive literature search was conducted in PubMed, EuropePMC, and OpenAlex. Randomized controlled trials (RCTs) published between 2015 and 2025 that compared OFA and OBA in adult patients (18 years) and reported PONV outcomes were included. Results of the 117 articles identified, five RCTs met the inclusion criteria. Although the limited number of studies limits the generalizability of the findings, this reflects the application of strict inclusion criteria that prioritize high-quality RCTs. Four studies (Clanet et al., 2024; Choi et al., 2022; Chen et al., 2023; Pratyusha et al., 2025) reported a statistically significant reduction in PONV in patients receiving OFA. In contrast, Yu et al. (2023) found no significant difference between OFA and OBA. Additionally, OFA was associated with reduced postoperative opioid consumption, which may contribute to lower PONV rates. Conclusion OFA demonstrates promising potential as a safe and effective alternative to OBA in reducing PONV. However, larger, well-designed randomized controlled trials are needed to confirm these findings and to further evaluate the impact of OFA on postoperative pain control and recovery quality.